Desirability Optimization Models to Create the Global Healthcare Competitiveness Index - DÖNMEZ, CEM ÇAĞRI (SPRINGER HEIDELBERG, 2020)
The aim of this research is to enhance desirability optimization models to create a global healthcare competitiveness index (GHCI) covering 53 countries with gross domestic product per capita (GDP PC) of over $10,000. The GHCI is defined as an index that reveals the progress and quality of the healthcare systems in countries providing their patients with easier access opportunities to healthcare services within the scope of this work. Methods of statistical analysis have been adopted together with optimization models and techniques in this research. The optimum and feasible values of the factors considered influential on objective functions have been determined as the basis of healthcare expenditure (HE) and GHCI in those relevant countries. Those released optimum outcomes are displayed between 0.64 and 0.66 in terms of desirability value. The GHCI values of those aforementioned countries range from 0 to 6. The computed average of the GHCI values of those countries is estimated as 2.4758. Finally, GHCI values of 53 countries have been calculated to set the current basis of desirability optimization models. These findings will be deemed as the basic essence of those prospective theories to be established for the future researches to constitute a new index to measure the competitiveness of healthcare systems in various countries all over the world.
Keywords: Desirability optimization models; Global healthcare competitiveness index; Healthcare systems; Healthcare expenditure; QUALITY MANAGEMENT; MANAGERIAL; DESIGN